Respuesta :

5.
-4n+ 7+ 2n= 1
⇒ (-4n+ 2n)+ 7= 1 (combine like terms)
⇒ -2n= 1-7
⇒ -2n= -6
⇒ n= -6/(-2)
⇒ n= 3

Final answer: B. 3~

6. 4(y-4)= 8
⇒ y-4= 8/4
⇒ y-4= 2
⇒ y= 2+4
⇒ y= 6

Final answer: D. 6~


Neuron
If you would like to solve the equation -4 * n + 7 + 2 * n = 1, you can do this using the following steps:

-4 * n + 7 + 2 * n = 1
-2 * n = 1 - 7
-2 * n = -6        /(-2)
n = -6 / (-2)
n = 3

The correct result would be B. 3.

If you would like to solve the equation 4 * (y - 4) = 8, you can do this using the following steps:

4 * (y - 4) = 8
4 * y - 4 * 4 = 8
4 * y = 8 + 16
4 * y = 24      /4
y = 24 / 4
y = 6

The correct result would be D. 6.
ACCESS MORE